Anti-inflammatory actions of herbal medicines in a model of chronic obstructive pulmonary disease induced by cigarette smoke - Possebon, Lucas [UNESP]; de Souza Lima Lebron, Isabella; Furlan da Silva, Ligia; Tagliaferri Paletta, Julia; Glad, Bruna Gabrieli; Sant'Ana, Monielle; Iyomasa-Pilon, Melina Mizusaki; Ribeiro Souza, Helena [UNESP]; de Souza Costa, Sara [UNESP]; Pereira da Silva Rodriguesa, Giselda; Pereira, Maria de Lourdes; de Haro Moreno, Andreia; et al. (Elsevier, 2018)
The effects of four medicinal herbs (Arctium lappa, Plantago major, Mikania glomerata Spreng and Equisetum arvense) with anti-inflammatory properties were evaluated in a chronic obstructive pulmonary disease (COPD) model. Wistar rats were exposed to cigarette smoke during 8 weeks and one of the groups was orally given a solution containing 4% of each alcoholic herbal extracts during the exposure period. Control group was not exposed to smoke or treated. Histopathological, immunohistochemical and biochemical analyzes were performed. Normal blood plasma levels of gamma glutamyl transferase indicated no toxicity of the administered herbal extracts. The treatment reduced leukocytes influx in bronchoalveolar lavage, mast cell and macrophages numbers in lungs, as well as prevented pulmonary congestion and tracheal metaplasia. Herbal mixture also decreased plasma inflammatory mediator levels and pulmonary expression of annexin A1 and nuclear factor-kβ. Our data indicate synergistic and protective effects of the used herbal medicines in animals exposed to cigarette smoke as a potential therapeutic strategy.
Keywords: COPD; Histopathology; Inflammatory mediators; Phytotherapy; Smoking